Instructional Leadership of School Administrators under the Office of Nongbualamphu Primary Education Service Area Office 1 - Srimuangbun, Adison (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objective of this article research were 1) to study of instructional leadership of school administrators as 2) to compare the leadership administrators of the school classified by status, and experienced in working differently, the performance difference is in the size of the school, 3) to developed guidelines of instructional leadership of school administrators as perceived by teachers under Nongbualamphu Primary Education Service Area Office 1. The samples of the study were total 328 : 56 administrators, 272 teachers under Nongbualamphu Primary Education Service Area Office 1. The research was a 5 level rating scale questionnaire with a reliability of 0.91. The statistics used for data analysis were percentage, mean, standard deviation, t-test and F-test (One-Way ANOVA). The research results were found that : 1. Academic leadership of School administrators overall and the aspects were found at a high. 2. The comparative data instructional leadership of school administrators, overall difference is statistically significant level. 01 and the analysis of comparative data instructional leadership of school administrators by experienced in working differently and size of the school, overall no difference. 3. Guidelines for the development of academic leadership of school administrators Main component at the lowest average, there are 3 main components: curriculum development preparation of an educational quality development plan the atmosphere of the educational institution.